(untitled) (Research, Society and Development, 2021)
The objective of the study was to identify the nurses’ perception of patient care in palliative care. This is an exploratory, descriptive, field research, with a qualitative character, 15 nurses from a private hospital in Paraná participated in the research. Data were collected through semi-structured interviews, containing sociodemographic variables and the professionals’ perception of palliative care. The results were analyzed using the Bardin method. It was observed that professionals refer to palliative care as one that offers comfort and pain relief, has family participation, is supported by a multidisciplinary team, in which the need for protocols and trained staff is observed. Nurses have a limited view regarding assistance to palliative care, which makes it difficult to provide qualified care.